The management of consumer consultation - Dugdage, Paul
This article analysis issues inherent in the interaction of public sector managers and consumers and advocates, presented from the management perspective. The debate about whether the new managerialism in the Australian Public Service promotes or undermines the values of qurity and access highlights the importance of a commitment on the part of management to the active participation of citizens in public service decision compared with consulting other public agencies, consultation with consumers does not take place within common authority structures. In contrast to private sector consumer consultation, public sector consultation is framed by citizens's expectations of the public sector to act in their inter
Keywords: Administrative Management; Public Policy; Consumers; Consultration